Monitoring of the Environmental Radioactivity at Elobeid Area, North Kordofan State, Sudan - IM Abdallsamed, Mohammed; M Ibrahim, Elhadi; A Salih, Mushaal; A Elhadi, Mohammed; D Mohammed, Ahmed; Mustafa, Hassan-A; A Elmansour, Asim; B Hussein, Mohammed; F Wady, Asha; M Mohammed, Muna (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
The present work deals with the monitoring of the radioactivity at Elobeid area, North Kordofan State, in the central Sudan. The ivestigation was done for the first time. Twelve basement rock samples were taken from three localities. The high resolution in situ gamma ray spectrometer system was used to examine the natural radioactivity levels. The mean weight values of the elemental and the activity concentration levels of 238U and 40K are 3.14 and 4.95 ppm with 39.7 and 1502 Bq/Kg in the migmatite gneisses, while the mean weight values and the activity concentration levels are 4.23 and 2.67 ppm with 52.5 and 809 Bq/Kg in the micaschist respectively. These results are conidered higher than the corresponding global average values proposed by United Nations Scientific Committee on the Effects of Atomic Radiation publications for normal radiation background areas, except the values for the 238U in the migmatite gneiss, approves the global average values. The study area requires further investigation of soil geochemistry, and the activity concentration levels of radionuclides in soil and groundwater. How to cite this article: Abdallsamed MI, Ibrahim EM, Salih MA et al. Monitoring of the Environmental Radioactivity at Elobeid Area, North Kordofan State, Sudan. J Adv Res Geo Sci Rem Sen s 2020; 7(1&2): 17-23.